Uji Diagnostik Gambaran Lesi Foto Thorax pada Penderita dengan Klinis Tuberkulosis Paru - Majdawati, Ana (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2010)
Chest radiography is one of examination to diagnose lung TB. More lesions in chest radiography as infiltrate, fibroinfiltrate, cavitas, calcification, pleural effusion, etc. often find in chronic lung diseases, especially lung TB. The aim of this study to determine the sensitivity and spesificity of clinical symptoms and chest x-ray lesions. This is a retrospective study of medical record of polyclinic and hospitalized patient of Bantul District Hospital year 2010. Diagnostic test research methods are based on the gold standard smear of sputum. There are 100 samples, consisting of 50 with clinical TB and 50 without, aged 18-50 year old with chest X-ray and sputum smear examination. The result showed the most clinical symptoms of TB are bloody cough and shortness of breath. Photo radiography obtained 33 patients with lesions infiltrates, 18 patients a combination of more than 3 lesions, 4 patients with fibroinfiltrate and 45 patients without lesions. Sensitivity and specificity of clinical symptoms of TB 74.5%, 75.5%, photo- fibroinfiltrate chest infiltrates 83.3%, 24.4% and a combination of more than 3 lesions 87.5%, 13.3%. Summing up the sensitivity of clinical symptoms, infiltrates-fibroinfiltrate and a combination of more than 3 lesions is quite high (> 70%), whereas low specificity (<70%).Foto thorax merupakan salah satu penunjang diagnostik tuberkulosis (TB). Lesi pada foto thorax seperti infiltrat, fibrosis, kalsifikasi, kavitas, effusi pleura maupun kombinasi lesi sering dijumpai pada penyakit radang kronik paru, terutama TB. Tujuan penelitian ini untuk mengetahui sensitifitas dan spesifisitas gejala klinis dan lesi foto thorax. Penelitian ini bersifat retrospektif dari catatan medik poliklinik dan bangsal RSUD Bantul tahun 2010. Ada 100 sampel, terdiri 50 dengan klinis TB dan 50 tanpa klinis TB, usia 18-50 tahun dengan foto thorax dan pemeriksaan sputum BTA. Metode penelitian uji diagnostik ini didasarkan pada baku emas sputum BTA. Hasil menunjukkan gejala klinis TB terbanyak adalah batuk berdarah dan sesak napas. Foto thorax didapatkan 33 pasien dengan lesi infiltrat, 18 pasien kombinasi lebih dari 3 lesi, 4 pasien dengan fibroinfiltrat dan 45 pasien tanpa lesi. Sensitifitas dan spesifisitas gejala klinis TB 74,5%, 75,5%, foto thorax infiltrat-fibroinfiltrat 83,3%, 24,4% dan kombinasi lebih 3 lesi 87,5%, 13,3%. Disimpulkan sensitifitas gejala klinis, infiltrat-fibroinfiltrat dan kombinasi lebih dari 3 lesi cukup tinggi (> 70%), sedangkan spesifisitasnya rendah (< 70%).